Unions in Crisis, Unions in Renewal? - Yates, Charlotte A. B. (Charlotte Alyce Bronwen); Fairbrother, Peter (Trade Unions in Renewal: A Comparative Study, 2003)
Describes the varying patterns of union governance and membership since 1945 in the five primarily English-speaking countries of Australia, Canada, Great Britain, New Zealand, and the US. Discusses union efforts at renewal in the 1990s as a result of declining membership and waning political influence.
Keywords: Commonwealth countries. Comparative industrial relations. Syndicats. Relations industrielles comparées. Sindicalismo. Sindicato. Comparative industrial relations. Labor unions; Labor unions. Labor unions; United States. Labor unions